Management of Special Health Literacy Services: A Multi-Site Study at Madrasah Aliyah - Wasiyem Wasiyem; Mesiono Mesiono; Abdurrahman Abdurrahman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates the management of special health literacy services at Madrasah Aliyah Negeri 1 Medan and Madrasah Aliyah Negeri 2 Model Medan, focusing on four management functions: planning, organizing, implementation, and supervision. Methodology: Using a qualitative multisite case study approach, data were collected through interviews, observations, and document analysis involving teachers, administrators, and students. Main Findings: The findings reveal that both madrasahs show a strong commitment to integrating health literacy into their educational practices; however, they differ in formalization and consistency. MAN 1 Medan exhibits a structured and well-documented planning process with clear coordination through the School Health Unit (UKS), whereas MAN 2 Model Medan relies on informal planning and teacher initiative. Implementation at both institutions includes curricular and extracurricular activities, but MAN 1 Medan demonstrates stronger institutional coordination. Supervision mechanisms are largely informal, lacking standardized evaluation systems. The study concludes that while collaborative practices between teachers, students, and external health institutions exist, formal frameworks and documentation are limited. Novelty/Originality of this study: The findings highlight the importance of developing structured systems, clear standard operating procedures, and formal evaluation mechanisms to enhance the effectiveness of health literacy services in religious schools. This study contributes to filling the research gap on health literacy management in madrasahs, offering practical insights for policymakers and educators in promoting health education that aligns with religious and cultural contexts.